ANALISIS PENDAPATAN ASLI DAERAH UNTUK MENILAI KINERJA KEUANGAN DAERAH PEMERINTAH KOTA BALIKPAPAN TAHUN ANGGARAN 2017-2021 - Kurniawan, Akhmad; Mutiarin, Dyah; Saputro, Muhammad Noor Cahyadi Eko (Prosiding University Research Colloquium, 2023)
This research aims to evaluate Balikpapan's financial health by analyzing the Realization Report of the City of Balikpapan APBD, specifically the ratio of independence, efficiency, and effectiveness of Local Own Revenue (PAD). The Budget Realization Report covers the fiscal years 2017 through 2021. Data analysis used a descriptive statistical approach. The results suggest that Balikpapan City's independence ratio is low and exhibits a constructive connection pattern between the 2017 and 2021 fiscal years, averaging just 29.99%. With an average success rate of 110.98% of the budgeted amount, PAD in Balikpapan City is very effective for the 2017-2021 fiscal year. The PAD efficiency ratio for the fiscal years 2017-2021 demonstrates the inefficient financial performance of Balikpapan City, with an annual average of 65.61%.